Antioxidant, Nutritional Properties, Microbiological, and Health Safety of Juice from Organic and Conventional ‘Solaris’ Wine (Vitis vinifera L.) Farming - Ireneusz Ochmian; Sebastian W. Przemieniecki; Magdalena Błaszak; Magdalena Twarużek; Sabina Lachowicz-Wiśniewska (Antioxidants)
This study investigated the technological parameters, microbiological, and functional properties of juice from Solaris grapes grown under conventional and organic farming systems to assess how these cultivation methods influence juice quality. The one-year study focused on key aspects such as the levels of health-promoting polyphenols, the presence of mycotoxins, and pesticide residues. Organic grapes showed greater bacterial and fungal diversity, with significant differences in dominant genera. Sphingomonas and Massilia were the predominant bacteria across both systems, while Erysiphe was more common in conventional grapes, and Aureobasidium was abundant in both. Despite the presence of genes for mycotoxin production, no mycotoxins were detected in the juice or pomace. Organic juice exhibited significantly higher levels of polyphenols, leading to enhanced antioxidant properties and improved technological characteristics, including lower acidity and higher nitrogen content. However, residues of sulfur and copper, used in organic farming, were detected in the juice, while conventional juice contained synthetic pesticide residues like cyprodinil and fludioxonil. These findings highlight that while organic juice offers better quality and safety in terms of polyphenol content and antioxidant activity, it also carries risks related to residues from organic treatments, and conventional juice poses risks due to synthetic pesticide contamination.